2017
DOI: 10.1002/cbdv.201700472
|View full text |Cite
|
Sign up to set email alerts
|

Tricalycoside, a New Cerebroside from Tricalysia coriacea (Rubiaceae)

Abstract: A new cerebroside, named as tricalycoside (1), was isolated from the CH 2 Cl 2 /MeOH (1:1) extract of twigs and leaves of Tricalysia coriacea using repeated silica gel open column chromatography followed by preparative TLC and Sephadex LH-20, together with six known compounds (2 -7). The structure of the new compound was determined by analysis of 1D-and 2D-NMR, MS data, chemical conversion, and by comparison of these data with those from the literature. Tricalycoside (1) possessed a weak antibacterial activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Compared with previously reported methods for the separation of OA and UA from natural products, our methodology is more feasible and practical. According to the experimental results in the reference, [23][24][25][26] for the preparative separation of OA and UA from natural products by silica gel column chromatography and dextran gel column chromatography, a more complicated experimental procedure was necessary in which the high consumption of organic solvents, a long separation time, irreversible sample adsorption and a low recovery of the solute would always be involved. For example, in the research by Huang'group, 24 silica gel column chromatography, dextran gel column chromatography and preparative HPLC were successively used to isolate and purify OA and UA.…”
Section: Selection Of Solvent Systems For Ph-zone-rening Countercurrmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with previously reported methods for the separation of OA and UA from natural products, our methodology is more feasible and practical. According to the experimental results in the reference, [23][24][25][26] for the preparative separation of OA and UA from natural products by silica gel column chromatography and dextran gel column chromatography, a more complicated experimental procedure was necessary in which the high consumption of organic solvents, a long separation time, irreversible sample adsorption and a low recovery of the solute would always be involved. For example, in the research by Huang'group, 24 silica gel column chromatography, dextran gel column chromatography and preparative HPLC were successively used to isolate and purify OA and UA.…”
Section: Selection Of Solvent Systems For Ph-zone-rening Countercurrmentioning
confidence: 99%
“…1,20 Although, there are several analytical methods available in literature for the separation of positional isomers, 21,22 it is difficult to separate OA and UA on the preparative scale due to their similar chemical properties. Several studies have been reported on the separation of OA and UA from natural products using silica gel column chromatography, [23][24][25][26] which is a timeand solvent-consuming procedure. Meanwhile, in order to achieve complete separation of the stereoisomers OA and UA by silica gel chromatography, a prechromatographic derivatization of OA and UA is necessary.…”
Section: Introductionmentioning
confidence: 99%